(untitled) (INNOVATIVE ECONOMY, 2021)
Bachynskyi V.I., Pomulіeva V.M. SIMPLIFIED ACCOUNTING IN SMALL BUSINESSES: THE REALITIES OF TODAY Purpose. The aim of the article is research of the peculiarities of the current state of simplified accounting in small enterprises and development of proposals for its improvement and identifies opportunities for further simplification. Methodology of research. The theoretical basis of the study were laws and normative and legal acts on regulation, organization, accounting and financial reporting in Ukraine, as well as scientific papers of domestic scientists on simplified accounting in small enterprises of Ukraine. The study used general scientific and specific methods: logical analysis, system approach, synthesis, induction and deduction, generalization (in the study of current norms and regulations on accounting regulation, accounting features), abstract and logical (in generalizing theoretical provisions and forming conclusions and proposals). Findings. A study of the peculiarities of simplified accounting in small enterprises is carried out. It is found out what special norms of simplified methods of accounting the current legislation contains for certain categories of small enterprises, the problems concerning their practical use by small enterprises are defined. Emphasis is placed on the insufficiency of simplified methods of accounting and the need to bring regulations on simplified accounting in line with modern realities. Proposals for improving accounting have been formed and the need for a single standard that regulates current issues of accounting in small enterprises and meets modern realities was substantiated. Originality. The urgent need to expand the methods of simplified accounting and the introduction of a single special legal act on accounting in small enterprises is substantiated. Practical value. The obtained research results and developed proposals can be used for further research, as well as in the development of regulatory documents. Key words: accounting, small enterprises, simplified forms of accounting, double entry, accounting registers, simplified chart of accounts, financial statements.